Penerapan Sistem Penjualan Dalam Kaitannya Dengan Penerimaan Kas Pada PT Bogor Raya Development - Hastoni, Hastoni; Wakhyudi, Wakhyudi (STIE Kesatuan, 2009)
System sales is a set of things or activities and the exchange of goods or services that interact each other and each other form one integrated unit to get other resources, such as cash, or promise to pay cash (receivables).The objective of this research is to understand the system in relation to the sales receipt of cash that has been run by the management of PT. Bogor Raya Development. Research conducted by the author is PT. Bogor Raya Development is located in the Village Sukaraja, Eastern District of Bogor 16710 Bogor Regency, West Java Province, Indonesia. PT. Bogor Raya Development is a company engaged in the field of property, sport club, golf club and event organizer and the hotel & resort that was first established by the PT. Reserved with Global Mandiri, PT. Asia Pacific Permai. Research methods used in the research essay is a descriptive method of research studies. Results of research showed that management implement sales activities based on the applicable customs procedures as the system owned by firm has not been updated so that it can not accommodate the business that the company has grown rapidly. This can complicate the measurement of the effectiveness of internal control of the company. In addition, the system has been run by the company less in accordance with the theory that has been described by the author in chapter II, this essay The interviews and the evaluation of the PT. Bogor Raya Development. This shows that PT. Bogor Raya Development has advantages in terms of reporting the exact time and the absence of a mechanism for the receipt of cash outside of working hours, cashier proshop. While the weakness of the PT. Bogor Raya Development is a company do not update the operating system procedures, which only bag tag written